2012
DOI: 10.1021/ml300283f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiproliferative Activities of Ottelione A Analogues

Abstract: Through the syntheses of its C-1 desvinyl, C-7 methylene, C-7 exocyclic ethylidene, and various C-3 phenylmethyl analogues, the structure−activity relationship of antimitotic ottelione A (4) against tubulin and various cancer cells was established. The results indicated that compound 4 was a colchicine-competitive inhibitor and that the C-1 vinyl group is unnecessary for its potency, whereas the C-7 exocyclic double bond is essential, possibly because of its irreversible interaction with tubulin. Further optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is interesting to look at the various synthetic methodologies devised for constructing the requisite bicyclic hydrindane skeleton and whole carbon framework by controlling the correct stereochemistry. These synthetic studies hold promise for preparing additional analogues of otteliones A and B with the aim of exploring their structure-activity relationships [41], which should be useful for the development of novel anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to look at the various synthetic methodologies devised for constructing the requisite bicyclic hydrindane skeleton and whole carbon framework by controlling the correct stereochemistry. These synthetic studies hold promise for preparing additional analogues of otteliones A and B with the aim of exploring their structure-activity relationships [41], which should be useful for the development of novel anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Our group has demonstrated a radical cyclization methodology for the enantioselective total synthesis for 1 . [ 13 ] In the following study, [ 17 ] we established the structure–activity relationship of 1 using the synthetic methodology. Compound 2 , the desvinyl and fluoro analog of 1 , was generated and found 6–38‐fold more potent than 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our study demonstrated that the exocyclic double bond was essential for the potency of 1 and 2 . [ 17 ] An irreversible nucleophilic 1,6‐addition would be responsible for their potency. [ 18,19 ] Although both 1 and 2 show potent in vitro activity, they might not be active in vivo due to their inherent instability in serum.…”
Section: Introductionmentioning
confidence: 99%
“…For example, H-3 is a dddd in 13 rather than a ddddd as it is in 1a or 1b. Finally, in light of i) continuing interest in the ottelione family of antitumor agents [14] and ii) the fact that no Mosher analyses have been described for any structural analogs related to the otteliones, we report here the results of a study of the Mosher esters of the alcohol derived from each of (+)-ottelione A (1a) and (+)-ottelione B (1b). (Figure 6).…”
mentioning
confidence: 99%
“…2.85 (2H, t, J = 7.5 Hz, H-1), 2.72 (2H, t, J = 7.5 Hz, H-2), 2.55 (2H, t, J =7.5 Hz, H-4), and 2.44 (2H, dt, J = 7.5, 7.5 Hz, H-5). See ref [18] for NMR spectral data for the corresponding bis-phenol (in methanol-d 4 (1S,3S,3aR,4S,7aS)-1-Ethenyl-1,2,3,3a,4,7a-hexahydro-3-[(3hydroxy-4-methoxyphenyl)methyl]-7-methylene-7H-indene-4-ol (14). To a solution of 1a (5 mg, 0.016 mmol) in MeOH (0.75 mL) was added CeCl 3 (6.5 mg, 0.017 mmol).…”
mentioning
confidence: 99%